FINANCIAL SELF-EFFICACY MEDIATES THE INFLUENCE OF FINANCIAL LITERATURE AND ATTITUDE ON FINANCIAL MANAGEMENT BEHAVIOR - I Gusti Ayu Ratih Permata Dewi (Bajang Institute, 2022)
The purpose of this study is for knowing the influence of literacy finance and attitude finance on managing finance and what self-efficacy is capable to moderate the influence of literacy finance and attitude finance on management finance. The researcher is interested in studying about behavior management finance personal to students Major Accountancy Warmadewa University's Faculty of Economics and Business Class year 2019. Ideally, Warmadewa University student Class of 2019 has been getting many subjects about accountancy finance nor management finance and already experienced manage finance during studying so that can be a fundamental knowledge to increase their behavior management finance wisely. The research population is 504 people. The researchers use the Slovin formula because in the withdrawal sample, quantity must be representative so that the results study could be generalized and the calculations are not needed table amount sample, however, could be conducted with formulas and simple calculations so that the amount sample of 100 people. Data collection in This study uses a research instrument in the form of a questionnaire. This research uses the Partial Least Square (PLS) analysis method. This result shows that literacy finance and attitude finance did not take an effect on financial management behavior. Furthermore, financial self-efficacy take positive effect and significant on financial management behavior, literacy finance takes an positive effect and significant on financial self-efficacy, while attitude finance did not take an effect on financial self-efficacy. The results also show that financial self-efficacy is able to mediate the effect of financial literacy on financial management behavior, but financial self-efficacy is not able to mediate the effect of financial attitudes on financial management behavor.